Imported penicillinase producing Neisseria gonorrhoeae becomes endemic in London. Issue 6 (December 1983) - Thin, R N; Barlow, D; Eykyn, S; Phillips, I
Abstract : We review all cases of gonorrhoea caused by penicillinase producing Neisseria gonorrhoeae (PPNG) seen between 1976 and 1983 at the sexually transmitted disease (STD) clinic of this hospital, which accounted for 11% of all such cases reported in that period in the United Kingdom. While the overall incidence of gonorrhoea remained relatively stable in this clinic, that of PPNG rose to 4.4% of all such cases by 1982. Until last year, 75% of these cases were imported, mainly from Nigeria and Ghana, but a marked change was seen in the second half of 1982, when 71% of cases were indigenous in origin. Casual partners and prostitutes in London were mentioned as the source of infection by 34% of patients, a much higher percentage than that seen previously. Such sources are notoriously difficult to trace and these figures show a very disturbing trend. Although rectal infection tends to be asymptomatic, PPNG was isolated in rectal cultures from two of five homosexuals and 19 of 26 women. There is therefore a risk that PPNG could spread rapidly through the homosexual population. We suggest that spectinomycin should no longer be the first drug of choice in the treatment of gonorrhoea caused by PPNG but should be replaced by the newer cephalosporins.